THE ROLE AND IMPORTANCE OF METHODOLOGY IN DEVELOPING STUDENTS’ ACADEMIC ABILITIES - Jumaeva Sanobar Absaatovna, Makhmudova Gulnoza Yuldoshevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article examines various approaches to studying students' organizational abilities. It presents the results of a study of the academic abilities of students majoring in teaching, and provides an analysis of the connections between students' organizational abilities and cognitive and psychomotor abilities (in the structure of academic abilities), as well as their academic performance.